The long and winding road: A comprehensive analysis of 50 years of Eysenck instruments for the assessment of personality. (1st February 2021) - Ruch, Willibald; Heintz, Sonja; Gander, Fabian; Hofmann, Jennifer; Platt, Tracey; Proyer, René T.
Abstract: Instruments for the assessment of the Eysenckian superfactors of personality, Psychoticism (P), Extraversion (E), and Neuroticism (N), were developed over the course of almost 50 years. Typically the convergence with the precursor was examined when a new scale was published. In the present study the continuity and change of the substance of P, E, and N is tested by administering all instruments to a sample simultaneously, together with measures of the Five-Factor Model. A factor analysis of the 19 markers of the PEN model clearly yielded three factors, with higher loadings for E and N compared to P. The superfactors typically were measured purely after the historically second (or third, for P) instrument. Analysing the item difficulty confirmed that the P items were softened during the revisions but this created a confounding of item difficulty and content: The earlier "tough" items (mostly low Agreeableness) were gradually complemented by "softer" items representing the presumed obverse of P, superego strength (mostly low Conscientiousness). Finally, a part of the observed heterogeneity of P was due to these differences in item difficulty. Overall, the EPQ-R seems to be the most valid single measure of the PEN model. Highlights: Compares Eysenck's personality scales using self-reports and expert ratings. Supports the three-factor structure of the PEN model across scale versions. Shows that the P scale became more reliable, but also "softer" over time. Indicates that the P scale shifted from low A to low C and low A. Tracks the heterogeneity of P to a confounding of item difficulty and item content.